Comparative study of anthropometric measurement and body composition between junior handball and volleyball players from Serbian National League comparative study between junior handball and volleyball players - Masanovic, B.; Milosevic, Z.; Corluka, M. (International Journal of Applied Exercise Physiology, 2018)
The purpose of this study was to describe anthropometric characteristics and body composition of junior handball and volleyball players from Serbian national league as well as to make comparisons between them. Sixty-one males were enrolled in the study, divided into three groups: fifteen handball players, fourteen volleyball players and thirty-two healthy sedentary subjects. All subjects were assessed for the anthropometric measures required for the calculation of body composition variables, using the standardized procedures recommended by established literature. Data was analysed using SPSS and the descriptive statistics were expressed as a mean (SD) for each variable, while the ANOVA and LSD Post Hoc tests were carried out to detect the effects of each type of sport. The results showed that there was no significant difference in body mass index, muscle content of body as well as for bone content of body among the groups, while a significant difference was found for body height, body weight as well as for fat content of body among the groups. Volleyball players were significantly taller than handball players and the subjects of the control group. Volleyball players were significantly heavier than the subjects of the control group. The percent of fat content in the body of volleyball players is significantly lower than the percent of fat content in the body of control group. These findings may give coaches from the region better working knowledge and suggest them to follow recent selection process methods and to be more careful during the recruitment.